Development state of MOOCs and 5G-based Meta Classrooms with synchronous teaching and assessment of students’ learning status - Huibin Liu; Zuoxun Fan (Humanities & Social Sciences Communications)
Abstract With the continuous informatization of teaching resources, massive open online courses (MOOCs) have flourished around the world in recent years. The top-ranked universities in America and China provide all kinds of open online courses, making education, especially higher education, cross-domain, borderless, and unconstrained by time–space constraints. However, online learning is not as effective as face-to-face learning because of the lack of connectivity between lecturers and the sense of isolation for students. Meanwhile, the interaction between lecturers and online learners is ineffective caused to the limitation of bandwidth and the lack of immersion. This paper states the development status of MOOCs in America and China, and analyzes the problems in current MOOCs. Further, the framework of 5G-based Meta Classroom equipped with a lecturer tracking system is proposed to solve the above problems and improve the effectiveness of online and offline teaching by realizing the synchronization between offline and online teaching based on 5 G wireless communication network and human detection technologies to decrease the sense of isolation for online learners. Furthermore, the prospect for Meta Classrooms is introduced to enhance experience and immersion in online learning by accommodating digital avatars of all students in a real classroom and online students in virtual classrooms. To verify the feasibility of Meta Classrooms, experimental results of short-term objectives of this study, global 5 G deployment, and implementation framework of 5G-enabled medium-term objectives, key technologies for achieving long-term objectives are given in detail.